The Effect Of Price And Product Quality On Purchase Interest In Zaennissa Snack Rengginang In Medan - Dinda Dwi Anggraini; Dian Septiana Sari; Hendra Utama; Wulan Dayu (Journal of Management, Economic, and Accounting, 2026)
This research aims to determine the influence of price and product quality on purchasing interest in Rengginang Zaennissa Snack Medan. This research used quantitative methods involving 72 respondents. Data collection was carried out using questionnaire distribution. The data obtained were analyzed using statistical formulas, namely using the normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis with the SPSS Version 23.0 program. The results of this research show that the results of this study indicate that the t-test results obtained a calculated t value of 94.012 greater than ttable 1.99 with a significance level of 0.000. Thus, H2 is accepted and Ho is rejected, which means that price has a positive and partially significant influence on consumer purchasing interest. The calculated t value of 42.462 is greater than ttable 1.99 with a significance level of 0.000. Thus, H2 is accepted and Ho is rejected, which means that product quality has a positive and partially significant influence on consumer purchasing interest. The calculated F value is 10127.477 with a significance level of 0.00o. Because the calculated F value of 10127.477 is greater than Ftable 3.13, it can be concluded that simultaneously the product quality and price variables have a significant influence on the dependent variable, namely purchasing interest.